Influence of test technique on sensitization status of patients on the kidney transplant waiting list - Gombos, Petra; Opelz, Gerhard; Scherer, Sabine; Morath, Christian; Zeier, Martin; Schemmer, Peter; Süsal, Caner (American journal of transplantation, 2013)
The exquisitely sensitive single antigen bead (SAB) technique was shown to detect human leukocyte antigen (HLA) antibodies in sera of healthy male blood donors. Such false reactions can have an impact on critical decisions, especially with respect to the determination of unacceptable HLA-antigen mismatches in patients awaiting a kidney transplant. We tested pretransplant sera of 534 patients on the kidney waiting list using complement-dependent cytotoxicity (CDC), enzyme-linked immunosorbent assay (ELISA) and SAB in parallel. Evidence of HLA antibodies was obtained in 5% of patients using CDC, 14% using ELISA, and 81% using SAB. Among patients without history of an immunizing event, 77% showed evidence of HLA antibodies in SAB. In contrast 98% of these patients were negative in ELISA and CDC. In patients without an immunizing event, SAB-detected antibodies reacted not always weakly but with mean fluorescence intensity (MFI) values as high as 14 440. High-MFI-value antibodies were found in some of these patients with HLA specificities that are rather common in general population, consideration of which would lead to unjustified exclusion of potential kidney donors. False SAB reactions can be unveiled by testing with additional antibody assays. Denial of donor kidneys to recipients based on HLA-antibody specificities detected exclusively in the SAB assay is not advisable.